Direct and Indirect Costs of Asthma Burden in Abu Dhabi: A Retrospective Analysis of Insurance Claims Data from 2015 to 2018 - Al Mazrouei K; Almannaei AI; Nur FM; Bachnak N; Alzaabi A (Dove Medical Press, 2021)
Khulood Al Mazrouei,1 Asma Ibrahim Almannaei,2 Faiza Medeni Nur,3 Nagham Bachnak,3 Ashraf Alzaabi4 1Pulmonology Department, Zayed Military Hospital, Abu Dhabi, United Arab Emirates; 2Department of Health, Healthcare Quality Division at the Abu Dhabi Health Authority, Abu Dhabi, United Arab Emirates; 3Healthcare Data and Analytics Division, Department of Health, Abu Dhabi Health Authority, Abu Dhabi, United Arab Emirates; 4Respiratory Medicine Division, Zayed Military Hospital, Abu Dhabi, United Arab EmiratesCorrespondence: Ashraf AlzaabiRespiratory Medicine Division, Zayed Military Hospital, Abu Dhabi, United Arab EmiratesTel +971 506 474 488Email ashrafalzaabi@uaeu.ac.aePurpose: Asthma causes a high economic burden on the health-care system. Previous research on the cost of asthma in Abu Dhabi was in 2011 and revealed high medical costs. This work aimed to estimate both direct and indirect costs of asthma with trend analysis over a period of four years.Patients and Methods: All data on medical costs, work absenteeism, and mortality were collected from the e-claims system of the national health insurance database. Medical costs included medication use, emergency room (ER) visits, non-ER visits, outpatient care, and hospitalization from 2015 to 2018. Indirect costs in terms of work absenteeism were calculated by multiplying the average daily income per employer by the number of workdays missed due to sick leaves documented in the database in 2019.Results: Over the years, the total medical costs increased from AED 161,843,698 in 2015 to AED 206,548,620 in 2018. The largest contribution was attributed to outpatient care, while hospitalization accounted for the smallest proportion of the total costs in 2018. Likewise, the mean annual per-patient cost in 2015 was AED 1119 and increased to AED 1162 in 2018. Indirect costs were estimated to be AED 27,482,319 resulting from 30,948 sick leaves in the year 2019 only.Conclusion: Asthma is a cause for huge expenditure from the health-care system perspective in Abu Dhabi. It also has a large impact on society through work absenteeism. Costs of asthma management are increasing every year, which suggests a call-to-action to improve the disease management status using cost-effective strategies.Keywords: asthma, direct cost, indirect cost, economic burden, Abu Dhabi